Contours of Knowledge: Epistemological Implications of Semantic Models in the Representation of the Art Exhibition Domain through the Lens of the OntoExhibit Ontology. - Rodríguez-Ortega, Nuria (Institute of Art History, Zagreb, 2024)
This paper delves into the epistemological impacts of deploying semantic web models within the cultural field, especially through the lens of the OntoExhibit ontology’s approach to modeling art exhibition ecosystems. It highlights OntoExhibit’s engagement with the socio-discursive practices and productions, the semantic and symbolic layers they generate, and the materiality of the art exhibition phenomenon, advocating for a nuanced reevaluation of materiality and agency in the context of the semantic models’ development. The article addresses the epistemological challenges and conceptual intricacies inherent in representing complex cultural ecosystems, underlining the imperative to critically examine the constraints and assumptions embedded in existent reference models, with a particular focus on CIDOC-CRM as the prevalent standard in cultural representation and documentation. The article suggests the need for a renovated and broader perspective that encompasses the evolving requirements of the formal
Keywords: Humanidades digitales; Ontologías (Recuperación de la información); Digital art history; Digital humanities; Computing humanities; Ontologies; Semantic web